2021
DOI: 10.3390/su13115764
|View full text |Cite
|
Sign up to set email alerts
|

The Coach–Athlete Relationship and Self-Talk in Turkish Athletes

Abstract: Background: The first purpose of the study was to evaluate the validity and reliability of the Automatic Self-Talk Questionnaire for Sports (ASTQS) in the Turkish language and the secondary purpose was to examine the relationship between the quality of the coach–athlete relationship and athletes’ self-talk. Methods: 477 athletes (females = 252, males = 225) completed the Turkish versions of the Coach–Athlete Relationship Questionnaire (CART-Q) and the ASTQS. Results: ASTQS showed good psychometric properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In fact, some studies, like the one developed by Thibodeaux and Winsler [19], found that higher levels of perceived coach mastery climate coincided with more reported use of positive self-talk. In this line, the recent study developed by Ada et al [20] found that the quality of coach-athlete relationships is related to the use of more positive self-talk and negatively to negative self-talk in sport. These works highlight the relevance of coach behaviors in the use of more positive organic self-talk.…”
Section: Contextual Variables Motivational Climate and Self-talkmentioning
confidence: 93%
“…In fact, some studies, like the one developed by Thibodeaux and Winsler [19], found that higher levels of perceived coach mastery climate coincided with more reported use of positive self-talk. In this line, the recent study developed by Ada et al [20] found that the quality of coach-athlete relationships is related to the use of more positive self-talk and negatively to negative self-talk in sport. These works highlight the relevance of coach behaviors in the use of more positive organic self-talk.…”
Section: Contextual Variables Motivational Climate and Self-talkmentioning
confidence: 93%